Price transmission in food and non-food product markets: Evidence from Mexico - Santiago Guerrero; Miriam Juárez; Daniel Sámano; Federico Kochen; Jonathan Puigvert (Banco de México, 2016)
We document the existence of asymmetric price transmission in Mexico for a wide variety of food and non-food products, in terms of magnitude and speed, for two segments of the supply chain: i) Producer (producer-wholesale) and ii) Consumer (wholesale-retail). We find that asymmetric price transmission is a common behavior in many of the good markets that we studied. However, there are important differences across stages of the supply chain: in the Producer segment, the analyzed food products exhibit larger asymmetries compared to non-food products, while we observe the opposite in the Consumer segment. The existence of these asymmetries may have important welfare effects on poor households, since they allocate a higher proportion of their expenditure for the acquisition of goods that present positive price asymmetries.
Keywords: D43; L13; L11; C25; 330; Price transmission; Positive price asymmetries; Food merchandises; Manufactured goods